Lending Targets and Marketing Performance at BPRS Puduarta Insani: Target Penyaluran Kredit dan Kinerja Pemasaran BPRS Puduarta Insani - Sari, Elina; Sugianto , Sugianto; Inayah , Nurul (Academia Open, 2025)
General background: Human resource management is a critical component of organizational success, particularly in the banking sector where marketing performance directly influences financial outcomes. Specific background: In the context of Sharia banking, institutions like PT. BPRS Puduarta Insani implement lending targets to guide marketing efforts. Knowledge gap: However, limited research has explored the dual impact—both motivational and burdensome—of such targets on employee performance in Islamic microfinance contexts. Aims: This study aims to analyze how the imposition of lending targets affects the work performance of Account Officers at PT. BPRS Puduarta Insani. Results: The findings reveal that while clear targets and associated rewards enhance motivation, focus, and creativity, excessively high targets induce stress and risk the compromise of prudential financing standards. Novelty: The study uniquely integrates qualitative insights to highlight the dynamic interplay between target-setting, compensation, and psychological well-being in a Sharia banking context. Implications: These results suggest that a balanced target-setting approach—aligned with market realities and employee capacity—can transform lending goals into performance drivers without undermining ethical lending standards. Highlight : Clear targets improve focus — Lending targets give Account Officers a structured direction to perform better. Rewards drive motivation — Incentives linked to target achievement enhance creativity and competitiveness. Excessive pressure risks performance — Unrealistic targets can lead to stress and compromise financing quality. Keywords : Sharia Bank, Marketing Performance, Compensation, Motivation, Lending Target